1980
DOI: 10.1002/pol.1980.170180224
|View full text |Cite
|
Sign up to set email alerts
|

Studies on polyyne polymers containing transition metals in the main chain. IV. Polymer synthesis by oxidative coupling of transition metal‐bis(acetylide) complexes

Abstract: The metal‐polyyne polymers consisting of transition metals and conjugated tetrayne systems where M represents Pt(PBu3)2 or Pd(PBu3)2 moiety were prepared by the oxidative coupling method and characterized by spectral analysis, associated with novel depolymerization giving binuclear transition metal complexes, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…Havinga et al [48] found o-dichlorobenzene (ODCB) to be a superior solvent for the oxidative polymerization of 1,8-nonadiyne under Hay conditions (O 2 , CuCl, TMEDA) to yield polymers with a molar mass of greater than 20 000. [49] In the presence of oxygen-sensitive products or reactants, large excesses of the Hay catalyst (CuCl, TMEDA) have been used to shorten the reaction time. We observed a similar advantage using this solvent in the oligomerization of platinum-bridged tetraethynylethenes under Hay conditions (Section 4.3).…”
Section: Copper-catalyzed Oxidative Homocoupling Reactionsðthe Glasermentioning
confidence: 99%
See 1 more Smart Citation
“…Havinga et al [48] found o-dichlorobenzene (ODCB) to be a superior solvent for the oxidative polymerization of 1,8-nonadiyne under Hay conditions (O 2 , CuCl, TMEDA) to yield polymers with a molar mass of greater than 20 000. [49] In the presence of oxygen-sensitive products or reactants, large excesses of the Hay catalyst (CuCl, TMEDA) have been used to shorten the reaction time. We observed a similar advantage using this solvent in the oligomerization of platinum-bridged tetraethynylethenes under Hay conditions (Section 4.3).…”
Section: Copper-catalyzed Oxidative Homocoupling Reactionsðthe Glasermentioning
confidence: 99%
“…Presumably ODCB keeps higher molecular weight oligomers in solution better, thereby ensuring the growth of longer polymers. [43,49] An interesting procedure, reported by Mori, Hiyama, and co-workers, allows direct coupling of trimethylsilyl-protected alkynes without previous removal of the protecting groups. Dichloromethane has been found to be another good solvent for both the oxidant and the polymer formed.…”
Section: Copper-catalyzed Oxidative Homocoupling Reactionsðthe Glasermentioning
confidence: 99%
“…Bei ihren Untersuchungen der oxidativen Dimerisierung heterocyclischer Alkine beobachteten Fritzsche und Hünig [47] eine starke Abhängigkeit der Reaktionsausbeute vom ver- [49] In Gegenwart sauerstoffempfindlicher Edukte oder Produkte sind zur Verkürzung der Reaktionszeit groûe Überschüsse an Hay-Katalysator (CuCl, TMEDA) verwendet worden. [43,49] Eine interessante Vorschrift von Mori, Hiyama und Mitarbeitern erlaubt die direkte Kupplung Trimethylsilyl-geschützter Acetylene ohne vorherige Entfernung der Schutzgruppen.…”
Section: Kupfer-katalysierte Oxidative Homokupplungsreaktionen ± Die unclassified
“…Two classes of platinum(II) r-alkynyl frameworks have been widely reported: one includes Pt mono-alkynyl and the others consist of Pt dialkynyl with trans-and cis-modes. Aiming at enhancing the device performances and tuning the photophysical and electroluminescent properties, a vast range of platinum-containing monomers and polymers have been prepared [36][37][38][39][40][41][42]. Raithby and co-workers reported a series of blue-luminescent [Pt(P n Bu 3 ) 2 ÀC"CÀXÀC"CÀ] (X = aromatic spacer) based polymers in the main chain in which the aromatic rings bearing extensive p-conjugation is useful to change the spectroscopic properties [43].…”
Section: Introductionmentioning
confidence: 99%